Integrating Sharia Contracts and Digital Technology in Indonesian Digital Wallet Platforms - Muhammad Robbani Ridho Robbani; Imron Rosyadi (Jurnal Hukum Ekonomi Syariah, 2025)
Digitalization in the field of Islamic finance is now a top priority, along with the rapid development of technology. This research discusses the implementation of digital contracts that comply with Sharia principles, while examining the challenges of integrating Islamic law with digital technology on electronic wallet platforms. Using a qualitative and descriptive-exploratory approach, data was collected thru literature studies and interviews with Islamic financial institutions, fintech practitioners, and users. The results show significant progress in the implementation of digital contracts, but there are still gaps in aligning Sharia rules with digital systems. The main challenges include the legal validity of digital contracts, the protection of personal data, and transaction security. This research emphasizes the importance of clear and flexible regulations to ensure that digital financial transactions remain in accordance with Sharia principles. Additionally, it is recommended to strengthen the legal framework, improve public understanding of Sharia-compliant fintech, and improve security infrastructure. Thru the analysis of real-world cases such as GoPay and LinkAja Syariah, this research proposes a model for developing digital contracts that are transparent, secure, and fully compliant with Sharia law. Overall, this research contributes to the broader discussion on Islamic digital finance by providing insights into the suitability of regulations and ethical digitalization, thus supporting the growth of a sustainable and inclusive Islamic financial ecosystem.